Analisis Pengaruh Fatwa MUI terhadap Perkembangan Ekonomi Syariah di Indonesia - Chairunisa Indri Rahmatika; Herlina Yustati (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aims to analyze the influence of the Indonesian Ulema Council (MUI) fatwas on the development of sharia economics in Indonesia. With the role of MUI as a fatwa authority, the guidance and decisions given influence the development of sharia economic sectors, such as sharia banking, sharia capital markets, and sharia insurance. This study uses a qualitative approach through case studies to examine how MUI fatwas influence the growth of sharia economics and its acceptance in society and sharia financial institutions. The results show that MUI fatwas play an important role in the development of sharia economics in Indonesia. The fatwas provide direction for sharia financial products that are in accordance with sharia principles, which contribute to the growth of sectors such as sharia banking, sharia capital markets, and sharia insurance. The fatwas also increase public trust in the sharia economy and encourage financial institutions to be more compliant with sharia principles.